Zanzibar Early Childhood Development : SABER Country Report 2013 - World Bank Group (World Bank, Washington, DC, 2016)
This report presents an analysis of the Early Childhood Development (ECD) programs and policies that affect young children in Zanzibar and recommendations to move forward. This report is part of a series of reports prepared by the World Bank using the SABER ECD framework and includes analysis of early learning, health, nutrition, and social and child protection policies and interventions in Zanzibar, along with regional and international comparisons.